The Effect of Experiential Marketing and Satisfaction on Patient Loyalty (North Lombok Regional Hospital) - Ahmad Haerul Umam; A Rohendi; Mira Veranita (Jurnal Manajemen, Akuntansi, Ekonomi, 2026)
This study examines the effect of experiential marketing on patient loyalty at North Lombok Regional Hospital, with patient satisfaction as a mediating variable. The originality of this research lies in applying the experiential marketing framework within a public healthcare setting in a developing region, where studies are still limited. The objective is to analyze how experience-based marketing strategies influence patient satisfaction and loyalty. The study employs a quantitative analytical observational design with a cross-sectional approach, collecting data from patients treated in the hospital’s emergency department between May and July 2025. Data were analyzed using regression analysis to examine the relationships among variables. The empirical results reveal that experiential marketing has a positive and significant effect on both patient satisfaction and patient loyalty, with satisfaction serving as a mediating factor. These findings confirm that effective implementation of experiential marketing enhances patient satisfaction and builds long-term loyalty, which are critical to hospital competitiveness in the public healthcare sector. The practical implication of this study is that North Lombok Regional Hospital should develop and consistently apply experience-based service standards to strengthen patient retention and improve its public reputation.